Sikap Toleransi dan Tipe Kepribadian Big Five pada Mahasiswa UIN Sunan Gunung Djati Bandung - Asti Meiza (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
Indonesia is a big country with high pluralism. Country like Indonesia requires a high tolerance attitude. This research aimed to obtain the description about tolerance in the students based on personality type. The participants were 350 UIN Sunan Gunung Djati Bandung’s students with quantitative approach. The variables were personality type and tolerance attitude. Personality types using a scale compiled from the Big Five theory formulated from the International Personality Item Pool (IPIP). Tolerance attitude was measured using the scale developed by van der Waltz. The results show that the type of personality Conscientious dominates the subject and there is no subject that has the Agreeableness type. From the four personality types, Analysis of Variance (Anova) found no significant difference in their tolerance attitudes. It seems that the majority of UIN Sunan Gunung Djati’s students have good moral values so they can tolerate the difference.